Analysis of students mathematical representation abilities in geometry learning in vocational high school - Euis Gusanti Sri Rahayu; Al Jupri (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The background of this research is the ability of students to solve the geometry problems in grade XII of vocational high school. Students are less able in solving problem, not using mathematical expression and are not persistent in expressing their argument. This research aims to know students ability in mathematical representation in solving geometry problems. This research used descriptive qualitative method. Data was collected by interview, documentation, and test. This research involved three students including three group : upper level students, middle level students, and lower level student. Data analysis techniques through data reduction, data presentation, and conclusions. Validity of data by using triangulation technique. The result showed that : (i) the average ability to solve geometry problems with visual representation is in medium category because it is able to draw the geometry to clarify the problem and solve the problem of geometry (ii) Mathematical representation expressions, in the upper level students is capable of making mathematical model but have not been able to solve the problem of geometry, while students with middle level and lower level have not been able to create mathematical models, (iii) The ability of word representation or written text of vocational high school students 14 Garut is still low because students have not written steps in solving geometry problems.